Gut Microbiota-Mediated Transformation of Coptisine Into a Novel Metabolite 8-Oxocoptisine: Insight Into Its Superior Anti-Colitis Effect - Ai, Gaoxiang; Huang, Ziwei; Cheng, Juanjuan; Xie, Jianhui; Zeng, Huifang; Liu, Yuhong; Li, Yucui; Huang, Xiaoqi; Chen, Jiannan; Su, Ziren (Frontiers in Pharmacology, 2021)
Coptisine (COP) is a bioactive isoquinoline alkaloid derived from Coptis Chinemsis Franch, which is traditionally applied for the management of colitis. However, the blood concentration of COP was extremely low, and its gut microbiota-mediated metabolites were thought to contribute to its prominent bioactivities. To comparatively elucidate the protective effect and underlying mechanism of COP and its novel gut microbiota metabolite (8-oxocoptisine, OCOP) against colitis, we used dextran sulfate sodium (DSS) to induce colitis in mice. Clinical symptoms, microscopic alternation, immune-inflammatory parameters for colitis were estimated. The results indicated that OCOP dramatically ameliorated disease activity index (DAI), the shortening of colon length and colonic histopathological deteriorations. OCOP treatment also suppressed the mRNA expression and release of pro-inflammatory mediators (TNF-α, IL-6, IL-18, IL-1β and IFN-γ) and elevated the transcriptional and translational levels of anti-inflammatory cytokine (IL-10) as well as the mRNA expression levels of adhesion molecules (ICAM-1 and VCAM-1). Besides, the activation of NF-κB pathway and NLRP3 inflammasome was markedly inhibited by OCOP. Furthermore, OCOP displayed superior anti-colitis effect to COP, and was similar to MSZ with much smaller dosage. Taken together, the protective effect of OCOP against DSS-induced colitis might be intimately related to inhibition of NF-κB pathway and NLRP3 inflammasome. And the findings indicated that OCOP might have greater potential than COP to be further exploited as a promising candidate in the treatment of colitis.